2017
DOI: 10.1016/j.seizure.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of eslicarbazepine-acetate in elderly patients with focal epilepsy: Case series

Abstract: ESL was well-tolerated and effective in elderly patients in a real-life setting over 1year, with a dose around 800mg/day. AE effects improved in most of who switched from CBZ or OXC to ESL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…The efficacy results were consistent with known previous data on ESL obtained from the phase III pivotal population [ 14 ]. With regards to other adjunctive ESL studies, an analysis of patients aged > 65 years included within the ESLIBASE study showed that, at 6 months, 24.1% of elderly patients were seizure free, similarly to our findings [ 20 ]. It is also similar to a retrospective open-label study of zonisamide as monotherapy/add-on treatment in focal and primary generalized epilepsy stratified by age, where seizure freedom was achieved in 27% of elderly patients, although 36% of the elderly epileptic patients received monotherapy, and were less refractory patients [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…The efficacy results were consistent with known previous data on ESL obtained from the phase III pivotal population [ 14 ]. With regards to other adjunctive ESL studies, an analysis of patients aged > 65 years included within the ESLIBASE study showed that, at 6 months, 24.1% of elderly patients were seizure free, similarly to our findings [ 20 ]. It is also similar to a retrospective open-label study of zonisamide as monotherapy/add-on treatment in focal and primary generalized epilepsy stratified by age, where seizure freedom was achieved in 27% of elderly patients, although 36% of the elderly epileptic patients received monotherapy, and were less refractory patients [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, clinical experience with ESL monotherapy in elderly patients has not been reported but ESL add‐on therapy has been reported to show better efficacy but more adverse effects in elderly than in younger patients (<65 years), despite the use of lower mean daily doses . Similarly, in the current study we found high seizure‐free rates at all the evaluation periods, with 67.3% of patients being seizure free for the entire follow‐up (vs 55.3% in the total population), the 1‐year retention rate was slightly lower (72.7%), and adverse events were more frequent (39.3%) in the elderly despite lower mean doses of ESL (720 mg/d at 12 months vs 879.3 mg/d in the total population).…”
Section: Discussionsupporting
confidence: 58%
“…In addition, hyponatremia resolved (from 128 to 138 mmol/L) in one patient and remained the same (133 mmol/L) in another patient after transitioning from OXC to ESL [ 32 ]. In a multicenter, retrospective case series of 29 elderly patients (> 65 years) with focal seizures who were treated with ESL, the tolerability profile improved in four of five patients who transitioned from CBZ or OXC to ESL because of AEs [ 36 ]. Overall, 3/29 (10.3%) patients developed hyponatremia, but only one developed symptoms (confusion) that resolved after withdrawal of ESL [ 36 ].…”
Section: Tolerability Profiles: Do These Differ?mentioning
confidence: 99%
“…In clinical trials of ESL adjunctive therapy, treatment regimens that included CBZ were shown to be less well tolerated than those that did not, despite attaining clinical efficacy [ 30 ]. There is also considerable evidence to demonstrate that patients transitioning from OXC or CBZ to ESL because of AEs experience improvements in tolerability [ 31 36 ]. Interestingly, improvements in quality of life and/or alertness were also reported [ 35 ].…”
Section: Tolerability Profiles: Do These Differ?mentioning
confidence: 99%